2008
DOI: 10.1111/j.1478-3231.2008.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic granulomas: histological and molecular pathological approach to differential diagnosis–a study of 442 cases

Abstract: Hepatic granulomas have a broad range of underlying aetiologies. With a combined histological, clinical, serological, and molecular approach, we were able to clarify the cause in 64% of the cases. Owing to the diverse prognosis and therapeutic implications, a detailed interdisciplinary workup of all liver biopsies with granulomatous lesions is mandatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
19

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(85 citation statements)
references
References 26 publications
1
65
0
19
Order By: Relevance
“…Drug-induced granulomatous hepatitis is also said to be an immunological disease involving hypersensitivity [17]. The present case showed a relatively long latency (about 2 weeks) between drug exposure and disease onset.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Drug-induced granulomatous hepatitis is also said to be an immunological disease involving hypersensitivity [17]. The present case showed a relatively long latency (about 2 weeks) between drug exposure and disease onset.…”
Section: Discussionmentioning
confidence: 64%
“…One report found that druginduced hepatic granuloma accounted for 11 (2.48 %) of 442 cases of biopsy-proven hepatic granuloma [17]. Many drugs have been associated with hepatic granuloma, the most common of which are allopurinol, sulfa drugs, chlorpropamide, and quinidine [18].…”
Section: Discussionmentioning
confidence: 99%
“…При повторной биопсии слизистой желудка вновь были выявлены эпителиоид-ные неказеифицирующие гранулемы. Кроме того, у больного была положительная проба Квейма и снижение диффузионной способно-сти легких при нормальной рентгенограмме органов грудной клетки [9,12]. В литературе встречаются описания случаев гранулематоз-ного гастрита, который можно диагностиро-вать при морфологическом исследовании в сочетании с клиническими и лабораторными методами.…”
Section: амурский медицинский журнал №2 (18) 2017unclassified
“…В редких случаях саркоидоз печени осложняется портальной гипертензи-ей или хроническим холестазом. Саркоидоз печени приводит к циррозу и портальной ги-пертензии только в 1% случаев [9]. Один по-добный случай описан в Индии в 2006 году [13].…”
unclassified
See 1 more Smart Citation